Depressive symptoms and multi-joint pain partially mediate the relationship between obesity and opioid use in people with knee osteoarthritis. Issue 9 (September 2022) - Carlesso, L.C.; Jafarzadeh, S.R.; Stokes, A.; Felson, D.T.; Wang, N.; Frey-Law, L.; Lewis, C.E.; Nevitt, M.; Neogi, T.; ,
Summary: Objectives: To assess the relation of obesity to opioid use in people with or at risk of knee osteoarthritis (OA), and the extent to which this association is mediated by number of painful joints or depressive symptoms. Methods: We used data from the Multicenter Osteoarthritis Study, a longitudinal cohort of older adults with or at risk of knee OA. Opioid use was identified by prescription medications and self-report. Obesity was defined as BMI ≥ 30 kg/m 2 . Multi-joint pain was assessed using a standardized body homunculus, and depressive symptoms using the Center for Epidemiological Studies Depression scale. We quantified the direct and indirect effect of obesity on opioid use through the number of painful joints or depressive symptoms using causal mediation analysis by natural-effects models. Results: We studied 2, 335 participants (mean age: 68; mean BMI 31 kg/m 2 ; 60% women). Persons with obesity had ∼50% higher odds of opioid use than those without. Estimates of indirect (mediated) effect by the number of painful joints and depressive symptoms suggested an increased odds of opioid use by 34% (odds ratio [OR] = 1.34, 95% CI: 1.04, 1.70) and 35% (OR 1.35, 95% CI: 1.05, 1.71), respectively, in obese vs non-obese individuals. The total effect of obesity on opioid use was higher in women than in men. Conclusions: Multi-joint pain and depressive symptoms partially explained greater opioid use among obese persons with knee OA, demonstrating that the negative impact of obesity on knee OA extends beyond its influence on knee pain and structural progression.